An experimental calibration of a sulfur-in-apatite oxybarometer for mafic systems. (15th November 2019) - Konecke, Brian A.; Fiege, Adrian; Simon, Adam C.; Linsler, Stefan; Holtz, Francois
Abstract: The incorporation of sulfur (S) into the apatite structure and the partitioning of S between apatite and silicate melt (DS ap/m ) have been proposed to vary systematically as a function of prevailing redox conditions. In this study, we experimentally equilibrated apatite with mafic silicate melt at 1000 °C, 300 MPa and a range of oxygen fugacity (fO2 ; log fO2 [ΔFMQ] = −1, 0, +0.3, +1.2, and +3 where FMQ is the fayalite-magnetite-quartz mineral redox buffer) to explore the partitioning behavior of S, including different oxidation states of S, between apatite and silicate melt. The data reveal that DS ap/m values increase systematically with increasing fO2, from 0.02± 0.01 at log fO2 [ΔFMQ] of −1 to 3.20 ± 0.19 at log fO2 [ΔFMQ] of +3. The bulk S content (∼0.37 and ∼0.28 wt.% S added) imparts a minor influence on DS ap/m at reducing conditions. Micro X-ray absorption near edge structure (μ-XANES) spectroscopy at the S K -edge was used to measure, in situ, the oxidation states of S in experimentally crystallized apatite. The S-XANES analyses reveal that with increasing fO2, apatite progressively incorporates S 6+ ≫ S 2− > S 4+ > S 1+ . The integrated S 6+ / Σ S peak area ratios and centroid energies (eV) were determined for apatite crystals in apatite from experiments at all fO2 conditions. The orientation effects occurring during S-XANES analyses of apatite were considered by merging spectra from multiple grains with random crystallographic orientation. The S-XANES data reveal that S 6+ / Σ S peak area ratios and the centroid energies increase systematically with fO2, demonstrating that the S 6+ / Σ S ratio in apatite can be used as an oxybarometer. The results demonstrate that both the S 6+ / Σ S and CeV calibration methods are highly sensitive in the redox range of ∼FMQ to ∼FMQ + 1.2 at the conditions and compositions evaluated in this study. As a result, the S-in-apatite oxybarometer is particularly applicable to mafic systems such as mid ocean ridge basalts (MORB), relatively reduced ocean island basalts (OIB), and back-arc basin basalt (BABB). Owing to the ubiquity of apatite in magmatic and magmatic-hydrothermal systems, measuring the concentration and oxidations state(s) of S-in-apatite has the potential to serve as a powerful sulfo- and oxy-barometer for a broad range of natural systems.